2021
DOI: 10.4049/jimmunol.2001107
|View full text |Cite|
|
Sign up to set email alerts
|

IL-21/IL-21R Signaling Aggravated Respiratory Inflammation Induced by Intracellular Bacteria through Regulation of CD4+ T Cell Subset Responses

Abstract: The IL-21/IL-21R interaction plays an important role in a variety of immune diseases; however, the roles and mechanisms in intracellular bacterial infection are not fully understood. In this study, we explored the effect of IL-21/IL-21R on chlamydial respiratory tract infection using a chlamydial respiratory infection model. The results showed that the mRNA expression of IL-21 and IL-21R was increased in Chlamydia muridarum–infected mice, which suggested that IL-21 and IL-21R were involved in host defense agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…FCRL5 plays important roles in autoimmunity with anti-phosphatidylserine antibodies produced by FCRL5 + T-Bet + atypical memory B cells [ 107 ]. IL-21 receptor (IL21R) promotes inflammation in myocardial infarction [ 108 ] and respiratory disease [ 109 ]. CEACAM1 is a coronavirus receptor on endothelial cells as we reported [ 54 ] and promotes vascular aging process [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…FCRL5 plays important roles in autoimmunity with anti-phosphatidylserine antibodies produced by FCRL5 + T-Bet + atypical memory B cells [ 107 ]. IL-21 receptor (IL21R) promotes inflammation in myocardial infarction [ 108 ] and respiratory disease [ 109 ]. CEACAM1 is a coronavirus receptor on endothelial cells as we reported [ 54 ] and promotes vascular aging process [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study had identified moderate disease of IL-21R −/− mice in the host response to C. muridarum infection with enhanced Th1 and Th17 responses (Supplemental Figure 1 and 2 ) [ 3 ]. Resistant IL-21R −/− mice also displayed reduced pulmonary inflammatory pathology with less inflammatory cell infiltration, thus Wright-Giemsa staining of lung cells was performed here and less proportion of pulmonary neutrophils were observed in IL-21R −/− mice than WT mice, especially at day 3 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Female wild-type mice (WT; C57BL/6) were purchased from the Huafukang Biotechnology (Beijing, China) with the license number of SCXK (Beijing) 2019-0008. IL-21R −/− mice on the same background were obtained with permission as gifts from Dr. Zhinan Yin (Nankai University, China) as previously described [ 3 ]. Six to 8-week old mice were randomly divided into different groups (3-4 mice per group) according to different infection time points, and all the mice studied were repeated at least 3 times.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations